2017
DOI: 10.1001/jama.2017.7115
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Insulin Degludec vs Insulin Glargine U100 on Hypoglycemia in Patients With Type 1 Diabetes

Abstract: clinicaltrials.gov Identifier: NCT02034513.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

15
193
2
6

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 194 publications
(216 citation statements)
references
References 23 publications
15
193
2
6
Order By: Relevance
“…Specifically, the daily dose of the IDeg component of IDegAsp was 26% lower than that of IDet in the comparator arm and the total daily dose of insulin was 15% lower with IDegAsp + IAsp vs IDet + IAsp. This is in agreement with previous results from treat‐to‐target trials, which demonstrated a lower end‐of‐trial daily insulin dose requirement with IDeg vs IDet and vs insulin glargine 100 units/mL (IGlar U100) and with IGlar U100 vs IDet …”
Section: Discussionsupporting
confidence: 93%
“…Specifically, the daily dose of the IDeg component of IDegAsp was 26% lower than that of IDet in the comparator arm and the total daily dose of insulin was 15% lower with IDegAsp + IAsp vs IDet + IAsp. This is in agreement with previous results from treat‐to‐target trials, which demonstrated a lower end‐of‐trial daily insulin dose requirement with IDeg vs IDet and vs insulin glargine 100 units/mL (IGlar U100) and with IGlar U100 vs IDet …”
Section: Discussionsupporting
confidence: 93%
“…Degludec is associated with tolerability and overall glycaemic control similar to other long‐acting insulin analogues, with the benefit of a reduced rate of overall symptomatic hypoglycaemic and severe hypoglycaemic events,21, 22, 23 which may have contributed to the lower rates of hypoglycaemia observed here compared with observations during the onset 1 study 14. In addition, in the present study, an improvement in glycaemic control, that is, a reduction in HbA1c of approximately 0.6% in each arm, was achieved with weekly titration of degludec (pre‐breakfast target, 4.0–5.0 mmol/L) over the eight‐week run‐in period.…”
Section: Discussionmentioning
confidence: 99%
“…These analogs are associated with less hypoglycemia, less weight gain, and lower A1C than human insulins in people with type 1 diabetes (16-18). Longer-acting basal analogs (U-300 glargine or degludec) may additionally convey a lower hypoglycemia risk compared with U-100 glargine in patients with type 1 diabetes (19,20).…”
Section: Insulin Therapymentioning
confidence: 99%